Respuestas
Respuesta dada por:
0
\frac{2}{5} + \frac{3}{4} = \frac{(2*4)+(5*3)}{20} = \frac{8+15}{20} = \frac{23}{20} ![\frac{2}{5} + \frac{3}{4} = \frac{(2*4)+(5*3)}{20} = \frac{8+15}{20} = \frac{23}{20} \frac{2}{5} + \frac{3}{4} = \frac{(2*4)+(5*3)}{20} = \frac{8+15}{20} = \frac{23}{20}](https://tex.z-dn.net/?f=+%5Cfrac%7B2%7D%7B5%7D+%2B+%5Cfrac%7B3%7D%7B4%7D+%3D+%5Cfrac%7B%282%2A4%29%2B%285%2A3%29%7D%7B20%7D+%3D+%5Cfrac%7B8%2B15%7D%7B20%7D+%3D+%5Cfrac%7B23%7D%7B20%7D+)
Preguntas similares
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años